Creation of oxygen vacancies to activate Fe2O3 photoanode by simple solvothermal method for highly efficient photoelectrochemical water oxidation. (6th April 2021) - Zhang, Lijing; Xue, Xiaoxiang; Guo, Tan; Bi, Lingling; Hu, Tao; Tan, Liqiang; Zhang, Xiaojie; Jiang, Jinlong; Hong, Kun; Zhang, Qianghua
Abstract: Photoelectric chemical (PEC) decomposition of water is regarded as one of the most promising ways to convert solar energy into hydrogen energy, which has attracted extensive attention from researchers at home and abroad. Among the numerous photoanode materials, α-Fe2 O3 is considered to be one of the most promising photocatalytic materials. However, due to the poor conductivity, short photogenerated charge life and high overpotential of water oxidation reaction, the development and application of α-Fe2 O3 is seriously hindered. Recently, the introduction of oxygen vacancies is an effective method to improve the efficiency of α-Fe2 O3 photoelectric conversion. In this work, oxygen vacancy was introduced in Fe2 O3 photoanode by simple solvothermal method with ethylene glycol as solvent at 160 °C. The photoelectric catalytic activity of eg-Fe2 O3 was significantly improved for solvothermal process. At 0.186 VSCE (1.23 VRHE ), the photocurrent density of eg-Fe2 O3 photoanode could reach 2.8 mA/cm 2, which is 1–2 orders of magnitude higher than that of pristine Fe2 O3 photoanode (0.1 mA/cm 2 ). XPS test results show that the solvothermal process with ethylene glycol at 160 °C introduces oxygen vacancy to Fe2 O3 photoanode. The tests of electrochemical impedance spectroscopy and photoelectrochemical impedance spectroscopy indicate that the introduction of the oxygen vacancy significantly improve the conductivity of the Fe2 O3 photoanode and reduces the resistance of charge transmission between the electrode catalytic material and the electrolyte, which are the main reasons for the improvement of photoelectric water oxidation activity. This work provides a new method for improving the photoelectrochemical water oxidation by iron oxide photoanode. Graphical abstract: Image 1 Highlights: The Fe2 O3 photoanode was activated by oxygen vacancies. The oxygen vacancy was introduced by simple solvothermal method at 160ºC. At 1.23 VRHE, the photocurrent density of eg-Fe2 O3 photoanode could reach 2.8 mA/cm 2 . The oxygen vacancy significantly improve the conductivity of the Fe2 O3 photoanode.